Plant phenology, growth and nutritive quality of Briza maxima: responses induced by enhanced ozone atmospheric levels and nitrogen enrichment. - Sanz, J; Bermejo, V; Muntifering, R; González-Fernández, I; Gimeno, B S; Elvira, S; Alonso, R (Environmental pollution (Barking, Essex : 1987), 2011)
An assessment of the effects of tropospheric ozone (O(3)) levels and substrate nitrogen (N) supplementation, singly and in combination, on phenology, growth and nutritive quality of Briza maxima was carried out. Two serial experiments were developed in Open-Top Chambers (OTC) using three O(3) and three N levels. Increased O(3) exposure did not affect the biomass-related parameters, but enhanced senescence, increased fiber foliar content (especially lignin concentration) and reduced plant life span; these effects were related to senescence acceleration induced by the pollutant. Added N increased plant biomass production and improved nutritive quality by decreasing foliar fiber concentration. Interestingly, the effects of N supplementation depended on meteorological conditions and plant physiological activity. N supplementation counteracted the O(3)-induced senescence but did not modify the effects on nutritive quality. Nutritive quality and phenology should be considered in new definitions of the O(3) limits for the protection of herbaceous vegetation.
Keywords: Dehesa annual grasslands; Nitrogen. Ozone; Nutritive quality; yield